REVITALISASI MAKNA HIJRAH DALAM AL-QUR’AN DAN RELEVANSINYA PADA MODERASI ISLAM - Ahlan Ahlan (Universitas Islam Malang, 2022)
The phenomenon of hijrah in today's modern society has a significant impact on changes in social attitudes. The change was based on the pros and cons in the meaning of the concept of Hijrah, the attitude of accusing each other and not respecting each other's views which led to social conflict so that it led to the loss of a sense of concern and a sense of togetherness between communities and religious communities. Revitalizing the concept is a reconstructive effort to create religious moderation, especially among Muslims themselves. Islamic moderation is an attempt to accept differences from each other's views, so as not to cause social problems. This article seeks to explain the important things that need to be done by everyone who conducts an assessment of the basic concepts that have implications for parallel and harmonious relations in society, especially on the issue of hijrah. People who emigrate should be an example for every spiritual and social action, not creating a problem of inequality and leading to estrangement in relations between fellow religious people. Hijrah taught by the Prophet, is the movement and change in the attitudes, habits and goals of a person's life which leads to a peaceful life that reflects the Islamic religion which is Rahmatallil 'aalamiin.